2016
DOI: 10.1002/jts.22090
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of PTSD Among Lower Manhattan Residents and Area Workers Following the 2001 World Trade Center Disaster, 2003–2012

Abstract: Group-based trajectory modeling was used to explore empirical trajectories of symptoms of posttraumatic stress disorder (PTSD) among 17,062 adult area residents/workers (nonrescue/recovery workers) enrolled in the World Trade Center (WTC) Health Registry using 3 administrations of the PTSD Checklist (PCL) over 9 years of observation. Six trajectories described PTSD over time: low-stable (48.9%), moderate-stable (28.3%), moderate-increasing (8.2%), high-stable (6.0%), high-decreasing (6.6 %), and very high-stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 32 publications
(58 reference statements)
2
41
0
1
Order By: Relevance
“…The four trajectories identified in WTC tower survivors are similar to those found in WTC police responders and the general population, which demonstrates that similar posttraumatic responses are found across populations of first responders and civilians (Feder et al., ; Galatzer‐Levy et al., ; Pietrzak, Feder, Singh et al., ). When considering other WTC cohorts, fewer tower survivors from the current study were identified as having stable low symptoms and more were identified as having chronically elevated PTSS (10.4%) than in samples of police responders (4.4–5.3%; Feder et al., ; Pietrzak, Feder, Singh et al., ); New York area residents and workers (8.0%; Welch et al., ); and rescue, recovery, and clean‐up workers (4.0%; Maslow et al., ). The disparate findings are likely dependent on several factors but may be due in part to the proximity and number of unique exposures experienced by WTC tower survivors who received little or no prior training or mental preparedness to deal with such events.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The four trajectories identified in WTC tower survivors are similar to those found in WTC police responders and the general population, which demonstrates that similar posttraumatic responses are found across populations of first responders and civilians (Feder et al., ; Galatzer‐Levy et al., ; Pietrzak, Feder, Singh et al., ). When considering other WTC cohorts, fewer tower survivors from the current study were identified as having stable low symptoms and more were identified as having chronically elevated PTSS (10.4%) than in samples of police responders (4.4–5.3%; Feder et al., ; Pietrzak, Feder, Singh et al., ); New York area residents and workers (8.0%; Welch et al., ); and rescue, recovery, and clean‐up workers (4.0%; Maslow et al., ). The disparate findings are likely dependent on several factors but may be due in part to the proximity and number of unique exposures experienced by WTC tower survivors who received little or no prior training or mental preparedness to deal with such events.…”
Section: Discussionmentioning
confidence: 74%
“…Studies of WTC first responders, rescue and recovery workers, and New York metropolitan–area residents have identified between four and six PTSS trajectories (Feder et al., ; Maslow et al., ; Pietrzak, Feder, Singh et al., ; Welch et al., ). Similar to findings related to WTC survivors, other studies of PTSS in various populations and in response to numerous types of traumas have typically found four trajectories: low symptom, recovering, worsening, and chronically elevated (see Bonanno & Mancini, ; Galatzer‐Levy, Huang, & Bonanno, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PTSD symptoms can last for many years [ 7 ]. Chronic PTSD symptoms among 9/11-exposed responders and civilians over 8–9 years of follow-up have been reported [ 8 10 ]. Pietrzak et al reported that 5.3% of police and 9.5% of non-traditional responders experienced chronic PTSD, while 8.5% of police and 6.7% of non-traditional responders reported delayed-onset PTSD [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The terrorist attack on the World Trade Center (WTC) in New York City on September 11, 2001 (9/11) has had long-term mental and physical health consequences[ 1 4 ]. Among adults, exposure to the events of 9/11 has been associated with mental health conditions including post-traumatic stress disorder (PTSD) and depression as well as physical health conditions including asthma and cardiovascular disease[ 1 , 5 7 ].…”
Section: Introductionmentioning
confidence: 99%